Three fleet reviews-and the South African Navy - Wessels, Andre (Faculty of the Humanities, University of the Free State, 2014)
Especially in the course of the past century and a half, many countries have organised fleet reviews to commemorate some or other important event in the history of the concerned country, or in the history of its navy. In this study, three major fleet reviews and concomitant naval events are described, discussed and analysed, in an effort to, inter alia, place the history of these particular events on record, to ascertain just how important they actually were, and to draw conclusions that could be of importance for future naval planning. The three fleet reviews that form the basis of this study are the South African (SA) Navy’s 75th anniversary celebrations (SAN75) in and off Simon’s Town and Cape Town in 1997, the 200th anniversary of the battle at Trafalgar that was commemorated in and off Portsmouth in 2005, and the 100th anniversary of the arrival of the Royal Australian Navy’s first warships in Sydney, which was commemorated in that city’s harbour and bay in 2013. Throughout, the emphasis will fall on the SA Navy’s role, for example in hosting SAN75 and participating in Trafalgar200; and its non-participation in the 2013 review.
Keywords: Fleet reviews; South African Navy; Trafalgar200; Festival of the Sea (Portsmouth); Royal Australian Navy; International Fleet Review (Sydney); Naval diplomacy